2009
DOI: 10.1523/jneurosci.5427-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes in Presynaptic and Axonal Transport Proteins Combined with Striatal Neuroinflammation Precede Dopaminergic Neuronal Loss in a Rat Model of AAV α-Synucleinopathy

Abstract: Little is known about key pathological events preceding overt neuronal degeneration in Parkinson's disease (PD) and ␣-synucleinopathy. Recombinant adeno-associated virus 2-mediated delivery of mutant (A53T) human ␣-synuclein into the substantia nigra (SN) under a neuron-specific synapsin promoter resulted in protracted neurodegeneration with significant dopaminergic (DA) neuron loss by 17 weeks. As early as 4 weeks, there was an increase in a dopamine metabolite, DOPAC and histologically, DA axons in the stria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
276
4
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 337 publications
(311 citation statements)
references
References 32 publications
29
276
4
2
Order By: Relevance
“…Specifically, a dying back of neurites was observed in the E57K group (Fig. 2H), resembling the axonal pathology described in PD (24,25). In addition, the neurites contained larger lump-like appearances within the E57K group than in the hWT α-syn (Fig.…”
Section: And E)supporting
confidence: 62%
See 1 more Smart Citation
“…Specifically, a dying back of neurites was observed in the E57K group (Fig. 2H), resembling the axonal pathology described in PD (24,25). In addition, the neurites contained larger lump-like appearances within the E57K group than in the hWT α-syn (Fig.…”
Section: And E)supporting
confidence: 62%
“…To analyze the distribution and levels of α-syn in the brains of rodents injected with the lentiviral particles, as previously described, samples were lysed and extracts fractioned into soluble and insoluble fractions by ultracentrifugation (25). Twenty micrograms of protein per lane were loaded into 4% to 12% SDS/PAGE gels and blotted onto PVDF membranes.…”
Section: Methodsmentioning
confidence: 99%
“…Lentiviral vectors expressing human wild type or mutant forms of α-synuclein have been shown to lead to a progressive loss of nigral dopaminergic neurons by 24-35% in rats over 5 months 37 whereas adenoviruses expressing human α-synuclein have been shown to decrease nigral dopaminergic neurons by up to 80% in as short as 6 weeks, however these results are less consistent. 11,12,[38][39][40][41] In our model, miR-7T-AsRed significantly reduced TH expression by one-third at week 16 and two thirds at week 24. However, staining with VMAT2, another neuronal marker showed that there was only a 30% loss of neurons at 24 weeks suggesting that the nigral neurons had downregulated their activity.…”
Section: Discussionmentioning
confidence: 55%
“…2, more than 70% of TH-positive neurons were GFP-positive 4 weeks after AAV injection into the SN, indicating efficient expression in DA neurons. It has been demonstrated that AAV-mediated ␣-synuclein delivery into the SN resulted in DA neuronal degeneration in both rat and mouse PD models (43,44). Transgenic mice overexpressing amino acid residues 1-130 of human ␣-synuclein developed selective dopaminergic neuronal loss in the substantia nigra pars compacta (45).…”
Section: ␣-Synuclein Cleavage By Mmp3mentioning
confidence: 99%